KUALITAS LAYANAN PADA GALERI INVESTASI UNIVERSITAS BUNDA MULIA DENGAN MENGGUNAKAN METODE SERVQUAL - Novita Novita; Lelly Christin (Business Management Journal, 2016)
The existence of Galeri Investasi at the campus is a part of the function of BEI to educate the public, especially students, about capital market investment. Galeri Investasi UBM aims to educate prospective generation of people to be able to play at the capital market in Indonesia. Galeri Investasi UBM has won Billionaire Campus Award. Achievements that have been achieved by the Galeri Investasi UBM also continue to be followed by an increase in service quality. Population of this research is the investor at Galeri Investasi UBM as listed as an active student. This study used a servqual models technique. The results showed that the strategic location of Galeri Investasi UBM should be maintained, while internet access / wifi in the Galeri Investasi UBM is the criterion that need to be improved because it has the lowest score .Keywords: servqual model, investment galery, stock market.